Severe hidradenitis suppurativa treatment using platelet‐rich plasma gel and Hyalomatrix. Issue 3 (9th July 2013) - Nicoli, Fabio; Balzani, Alberto; Lazzeri, Davide; Gentile, Pietro; Chilgar, Ram M; Di Pasquali, Camilla; Nicoli, Marzia; Bocchini, Ilaria; Agovino, Annarita; Cervelli, Valerio
Abstract Hidradenitis suppurativa (HS) can be a debilitating chronic disease. The underlying cause of the disease is still not clear. HS may be managed through numerous different medical or surgical procedures. Surgical treatment may consist of local excisions and reconstruction using a variety of methods: perforator flaps, skin grafts, local flaps, primary closure or secondary wound healing with vacuum and other devices. This report describes our experience with surgical excision and closure using platelet‐rich plasma (PRP) gel and Hyalomatrix PA (HPA) in a patient with severe HS involving most of the body surface. We treated the patient with resection of severe HS of the nuchae and closure with PRP gel prepared with the RegenKit® to promote neovascularisation and HPA, a delivery system for hyaluronic acid, to induce a neodermis at the wound bed and to stimulate regeneration in a humid and protected environment. Complete wound healing was achieved after 2 months. The obtained result proved the efficacy of this treatment without complications. No recurrence was observed during the 1 year after the surgical procedure. Severe HS can be safely and effectively managed with wide excision, PRP gel and Hyalomatrix to achieve a successful outcome.